Diversidade Ictiofaunística e Ecologia reprodutiva de uma espécie nativa de peixe da Bacia Piranhas-Assu, RN - Nascimento, Wallace Silva do (2010)
The Caatinga biome is rich in endemic fish species fauna. The present study the results of fish faunal surveys conducted in the hydrographic basin of Piranhas-Assu of the Brazilian Caatinga biome. The fish samples collected were distributed in four orders (Characiformes, Perciformes, Siluriformes and Synbranchiformes), 11 families (Characidae, Curimatidae, Auchenipteridae, Anostomidae, Prochilodontidae, Erythrinidae, Cichlidae, Sciaenidae, Heptapteridae, Loricariidae, Synbranchidae) and 22 species, of which 17 are endemic and five have been introduced from other basins. The order Characiformes was the most representative in number of species (46,35% ) followed by Perciformes (35,38%), Siluriformes (17,44%) and Synbranchiformes (0,5%). The Nile tilapia, Oreochomis niloticus, the only exotic species, was most expressive in number of individuals (24.92%) followed by the native species piau preto, Leporinus piau (18,77 %). Considering the relative frequency of occurrence of the 22 species, 13 were constant, five were accessory and four were occasional. This study investigated the reproductive ecology of an endemic fish black piau, Leporinus piau from the Marechal Dutra reservoir, Acari, Rio Grande do Norte. Samplings were done on a monthly basis from January to December 2009, and a total of 211 specimens were captured. The environmental parameters such as rainfall, temperature, pH, electrical conductivity and dissolved oxygen of water were recorded. The sampled population showed a slight predominance of males (55%), however females were larger and heavier. Both sexes of L. piau showed positive allometric growth, indicating a higher increase of weight than length. The first sexual maturation of males occurred at smaller size, with 16.5 cm in total length than females (20.5 cm). During the reproductive period, the condition factor and gonadosomatic index (GSI) of L. piau were negatively correlated. This species has large oocytes with a high mean fecundity of 54.966 with synchronous oocyte development and total spawning